Hamiltonian structure and asymptotic symmetries of the Einstein-Maxwell system at spatial infinity - Marc Henneaux; Cédric Troessaert (Journal of High Energy Physics, 2018)
Abstract We present a new set of asymptotic conditions for gravity at spatial infinity that includes gravitational magnetic-type solutions, allows for a non-trivial Hamiltonian action of the complete BM S 4 algebra, and leads to a non-divergent behaviour of the Weyl tensor as one approaches null infinity. We then extend the analysis to the coupled Einstein-Maxwell system and obtain as canonically realized asymptotic symmetry algebra a semi-direct sum of the BM S 4 algebra with the angle dependent u(1) transformations. The Hamiltonian charge-generator associated with each asymptotic symmetry element is explicitly written. The connection with matching conditions at null infinity is also discussed.